2019
DOI: 10.3853/j.2201-4349.71.2019.1716
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence in support of the recognition of the Kaputar Rock Skink, one of New South Wales’ most range-restricted vertebrate species

Abstract: The existence of the Kaputar Rock Skink, a morphologically distinct Egernia population restricted to the Nandewar Ranges in northern New South Wales, has been known for decades. However, no comprehensive description or diagnosis of the taxon has been published in the scientific literature, and its distinctiveness largely assumed. As part of a study investigating the genetic differentiation of faunal populations on the Nandewar Range, comparisons between the Kaputar Rock Skink and east Australian Egernia striol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…However, genetic analysis of the E. striolata specimens sampled at Coolah Tops showed only slight differentiation from populations sampled further east and northeast on the Central and Northern Tablelands (Sadlier et al, 2019). Recently a population of 'striolata' group skinks from high elevation at Mt Kaputar was recognized as a distinct species (Sadlier et al, 2019). Detailed genetic analysis of the E. cunninghami samples from Coolah Tops is currently underway, but initial results show this population to be genetically differentiated from populations to the east on the Walcha basalts and Moonbi granite ranges.…”
Section: Reptiles and Amphibiansmentioning
confidence: 82%
See 1 more Smart Citation
“…However, genetic analysis of the E. striolata specimens sampled at Coolah Tops showed only slight differentiation from populations sampled further east and northeast on the Central and Northern Tablelands (Sadlier et al, 2019). Recently a population of 'striolata' group skinks from high elevation at Mt Kaputar was recognized as a distinct species (Sadlier et al, 2019). Detailed genetic analysis of the E. cunninghami samples from Coolah Tops is currently underway, but initial results show this population to be genetically differentiated from populations to the east on the Walcha basalts and Moonbi granite ranges.…”
Section: Reptiles and Amphibiansmentioning
confidence: 82%
“…Previously a lack of samples from Coolah Tops had meant no genetic study had been conducted assessing the degree of isolation of the Coolah Tops populations. However, genetic analysis of the E. striolata specimens sampled at Coolah Tops showed only slight differentiation from populations sampled further east and northeast on the Central and Northern Tablelands (Sadlier et al, 2019). Recently a population of 'striolata' group skinks from high elevation at Mt Kaputar was recognized as a distinct species (Sadlier et al, 2019).…”
Section: Reptiles and Amphibiansmentioning
confidence: 99%
“…The diagnosis purported a single morphological feature (enlarged paravertebral scales) that is not unique to this species, but is shared by all congeners within the Egernia striolata species-complex (Shea and Sadlier 1999). As such, the Kaputar rock skink was not formally recognised as distinct until a recent study led by the Australian Museum confirmed the Mt Kaputar populations as a valid taxon based on combined genetic and morphological evidence (Sadlier et al 2019). Apart from this re-description study, the species has received little research or conservation attention.…”
Section: Introductionmentioning
confidence: 99%
“…Such is the case for the Kaputar rock skink (Egernia roomi). The species was formally recognised as a separate species (Sadlier et al 2019) only a month and a half prior to when fire began on Mount Kaputar in October 2019; a fire that eventually burned over 40% of the national park before it was extinguished a month later (DPIE 2021). Known only from an extremely limited area and elevational band of rock habitat (Sadlier et al 2019), this species was immediately flagged as a conservation concern (Legge et al 2022a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation